Nano hydrogen-resistant internal coating for natural gas pipeline and preparation method of nano hydrogen-resistant internal coating

By preparing Ni-ZrO2/SiC/Si3N4 composite nano-hydrogen-resistance inner coating on natural gas pipelines, the problem that existing pipelines cannot meet the risks of high concentration hydrogen energy transport and hydrogen failure is achieved, and higher hydrogen resistance performance and safety are achieved.

CN119530911APending Publication Date: 2025-02-28PETROCHINA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311087885.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing natural gas pipelines cannot meet the high concentration of hydrogen energy transmission, resulting in limited large-scale hydrogen energy transmission and a risk of hydrogen failure, which seriously affects pipeline safety and efficiency.

Method used

The Ni-ZrO2/SiC/Si3N4 composite nano-hydrogen-resisted inner coating was prepared by electrochemical deposition. By doping SiC, ZrO2 and Si3N4 nanoparticles in the nickel-based material, a dense hydrogen barrier layer was formed to physically isolate the hydrogen gas from contact with the pipeline and reduce the permeability of hydrogen atoms.

Benefits of technology

It significantly improves the hydrogen resistance performance of natural gas pipelines, reduces the risk of hydrogen failure, extends the service life of the pipeline, and supports the safe and low-cost transportation of high-concentration hydrogen energy.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a nano hydrogen-resistant internal coating for a natural gas pipeline and a preparation method. The nano hydrogen-resistant internal coating comprises a substrate material and nano particles doped in the substrate material, the substrate material is selected from an oxide or chloride taking nickel as a substrate; the nano particles doped in the substrate material comprise SiC nano particles, ZrO2 nano particles and Si3N4 nano particles; and the Ni-ZrO2 / SiC / Si3N4 composite nano hydrogen-resistant inner coating is formed. According to the nanometer hydrogen-resistant internal coating, an optimal plating solution formula is developed based on an electrochemical deposition method, the nanometer hydrogen-resistant internal coating with good hydrogen-resistant performance and high compactness for the natural gas pipeline is prepared by continuously optimizing process parameters, contact between hydrogen and the pipeline is physically isolated, damage of hydrogen atoms to the pipeline is eliminated, and the hydrogen-resistant performance of the hydrogen-doped pipeline is improved; the problems that a hydrogen-doped natural gas pipeline is low in hydrogen doping proportion and high in failure risk are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of natural gas hydrogen-blended transportation pipelines, and in particular to a natural gas pipeline nano hydrogen-barrier inner coating and a preparation method thereof. Background Art

[0002] Hydrogen is recognized as the clean energy with the greatest development potential. Although my country has made significant progress in hydrogen energy technology in recent years, there is still a certain gap in the main links of the industrial chain such as hydrogen energy preparation, storage and transportation compared with the United States, the European Union and Japan, especially the problem of high cost of hydrogen energy preparation, storage and transportation. At present, there is no mature hydrogen energy transmission pipeline network at home and abroad, which seriously restricts the rapid development of hydrogen energy. However, the construction of pure hydrogen transmission pipeline network will face huge investment costs and immature technology. Therefore, low-cost, safe and efficient transportation of hydrogen is an urgent problem to be solved in the industry. To achieve long-distance and large-scale transportation of hydrogen energy, pure hydrogen pipelines and natural gas pipelines with hydrogen can be used. However, the construction cost of pure hydrogen pipelines is high, and it also involves problems such as difficult site selection and planning obstructions. Therefore, based on the natural gas pipeline network that has been built at home and abroad, the natural gas mixed with hydrogen mode will be adopted to achieve large-scale transportation of hydrogen energy, thereby creating huge economic and social benefits.

[0003] A lot of research has been carried out at home and abroad on the mixed transportation of natural gas with hydrogen, but it mainly focuses on exploring the compatibility of pipelines and hydrogen blending ratios. At present, natural gas mixed transportation with hydrogen still faces two major problems. The first problem is that the hydrogen blending ratio is low. The highest hydrogen blending ratio in foreign countries can reach 50%. Studies have shown that a hydrogen blending ratio below 20% has no obvious impact on the pipeline, while the domestic hydrogen blending ratio is about 5%-10%, which restricts the large-scale transportation of hydrogen energy; the second problem is that after hydrogen is blended into the natural gas pipeline, hydrogen atoms can penetrate into the pipeline body, forming small cracks, changing the mechanical properties of the pipeline, and the risk of hydrogen-induced failure increases sharply, thereby causing energy supply interruptions, facility damage, casualties and other serious consequences. The higher the hydrogen blending ratio, the greater the risk of hydrogen-induced failure. The existing pipeline cannot meet the high-concentration hydrogen energy transportation. Therefore, new natural gas pipelines should comprehensively consider factors such as future energy demand and safe operation of pipelines, improve the hydrogen resistance of pipelines, and ensure the safety of pipelines facing hydrogen.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] The problem with the prior art is that the existing natural gas pipelines cannot meet the requirements of high-concentration hydrogen transportation, which restricts the large-scale transportation of hydrogen. The purpose of the present invention is to provide a natural gas pipeline nano-hydrogen barrier inner coating and a preparation method thereof. Based on the electrochemical deposition method, an optimal plating solution formula is developed, and by continuously optimizing the process parameters, a natural gas pipeline nano-hydrogen barrier inner coating with good hydrogen barrier performance and strong density is prepared, which physically isolates hydrogen from contact with the pipeline, eliminates the damage of hydrogen atoms to the pipeline, improves the hydrogen barrier performance of the hydrogen-blended pipeline, and solves the problems of low hydrogen blending ratio and high failure risk of hydrogen-blended natural gas pipelines.

[0006] The present invention is achieved through the following technical solutions:

[0007] A natural gas pipeline nano hydrogen barrier inner coating, comprising a base material and nanoparticles doped in the base material;

[0008] The base material is an oxide or chloride based on nickel;

[0009] The nanoparticles doped in the base material include SiC nanoparticles, ZrO2 nanoparticles and Si3N4 nanoparticles;

[0010] A Ni-ZrO2 / SiC / Si3N4 composite nano hydrogen barrier inner coating is formed.

[0011] The present invention selects nickel-based oxides or chlorides with high molecular bond energy and dense crystal structure as base materials, which can prevent hydrogen atom penetration. Since the diffusion rate of hydrogen in the nano-doped composite coating is much lower than its diffusion rate in the metal, the present invention dopes SiC, ZrO2 and Si3N4 nanoparticles in the coating, and the C-, O- and N-bonds formed in SiC, ZrO2 and Si3N4, as well as the "hydrogen traps" formed at the interface between the monolayers can effectively inhibit the penetration of hydrogen. In addition, a large number of dangling bonds and molecular vacancies generated by nanoparticle doping can consume the energy of hydrogen atoms, so that they do not have enough energy to break free from the molecular bonds, thereby achieving the capture of hydrogen atoms and ensuring the formation of a material structure that effectively blocks the penetration of hydrogen atoms.

[0012] Further, the doping ratio of the SiC nanoparticles is 1 g / L to 3 g / L;

[0013] The doping ratio of the ZrO2 nanoparticles is 1 g / L to 2 g / L;

[0014] The doping ratio of the Si3N4 nanoparticles is 1 g / L to 3 g / L.

[0015] Furthermore, the average particle size of the SiC nanoparticles, ZrO2 nanoparticles and Si3N4 nanoparticles is 20nm~40nm. Doping nanoparticles of different sizes can refine the grains, reduce the porosity in the ceramic coating, and improve the surface morphology of the ceramic coating, so as to further prevent hydrogen penetration. The average particle size of the nanoparticles is selected to be 20nm~40nm, which forms a new stable molecular structure with the substrate material, blocks the grain boundary channels for hydrogen atom penetration, thereby achieving an effective hydrogen barrier effect.

[0016] Furthermore, the Ni-ZrO2 / SiC / Si3N4 composite nano hydrogen barrier inner coating is prepared by an electrochemical deposition process.

[0017] Furthermore, the deposition liquid formula in the electrochemical deposition process is NiSO4·6H2O: 240-280 g / L, NiCl2·6H2O: 45-60 g / L, H3BO3: 30-40 g / L, sodium dodecyl sulfate: 0.23-0.4 g / L, ZrO2: 20 mL, SiC: 20 mL, and Si3N4: 20 mL.

[0018] Furthermore, the preparation parameters of the electrochemical deposition process are: electrodeposition time is 8 to 10 hours, electrodeposition temperature is 40 to 60°C, and electrodeposition average current density is 10 to 20 mA / cm 2 , the pH value of the electrochemical deposition solution is 9-10, and the stirring speed of the electrochemical deposition solution is 200r / min.

[0019] The present invention also provides a method for preparing a nano hydrogen barrier inner coating for a natural gas pipeline, comprising the following steps:

[0020] (1) Pretreatment of pipe fittings: Prepare a degreasing formula according to a certain ratio, use clean water, degreasing agent, etc. to degrease the pipe fittings to remove surface oil and impurities, and then use sandpaper, grinder, etc. to grind the pipe fittings to ensure that the surface is smooth and free of rust, burrs, oil stains and other impurities;

[0021] (2) Preparation of inner coating: The pipes that have been pre-treated by degreasing and rust removal are placed in an electrochemical deposition solution for preparation. The test uses a constant current pulse power supply and a heating rod to heat the plating solution to 40-60°C. The electroplating time is 8-10 hours. The average current density during the electroplating process is 10-20 mA / cm 2 By continuously optimizing the process parameters such as the content of the electrochemical deposition liquid, rotation speed, time, temperature, current density and pH, a Ni-ZrO2 / SiC / Si3N4 composite hydrogen-barrier inner coating with a thickness of 5 to 20 μm and a porosity of <5% is obtained on the inner wall of the pipe fitting, which is tightly bonded to the inner wall of the pipeline. It has the advantages of good hydrogen-barrier performance, strong durability, high bonding, strong density, high smoothness and long service life.

[0022] Furthermore, the degreasing agent has the following formula: OP-1: 0.5 g / L, Na2CO3: 50 g / L, Na3PO4: 70 g / L, NaOH: 10 g / L.

[0023] Furthermore, the formula is NiSO4·6H2O: 240-280 g / L, NiCl2·6H2O: 45-60 g / L, H3BO3: 30-40 g / L, sodium dodecyl sulfate: 0.23-0.4 g / L, ZrO2: 20 mL, SiC: 20 mL, Si3N4: 20 mL.

[0024] Furthermore, the preparation parameters of the electrochemical deposition process are: electrodeposition time is 8 to 10 h, electrodeposition temperature is 40 to 60 ° C, and electrodeposition average current density is 10 to 20 mA / cm 2 , the pH value of the electrochemical deposition solution is 9-10, and the stirring speed of the electrochemical deposition solution is 200r / min.

[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0026] The present invention proposes a natural gas pipeline nano hydrogen barrier inner coating and a preparation method thereof. Based on the electrochemical deposition method, an optimal plating solution formula is developed, and by continuously optimizing the process parameters, a natural gas pipeline nano hydrogen barrier inner coating with good hydrogen barrier performance and strong density is prepared, which physically isolates hydrogen from contact with the pipeline, eliminates the damage of hydrogen atoms to the pipeline, improves the hydrogen barrier performance of the hydrogen-doped pipeline, and solves the problems of low hydrogen doping ratio and high failure risk of hydrogen-doped natural gas pipelines. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0028] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid obscuring the present invention, well-known structures, circuits, or methods are not specifically described.

[0029] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or subcombination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0030] In the description of the present invention, terms such as "front", "rear", "left", "right", "up", "down", "vertical", "horizontal", "high", "low", "inside" and "outside" to indicate directions or positional relationships are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred device or element must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as limiting the scope of protection of the present invention.

[0031] Example 1

[0032] The embodiment of the present invention provides a natural gas pipeline nano hydrogen barrier inner coating, comprising a base material and nanoparticles doped in the base material;

[0033] The base material is an oxide or chloride based on nickel;

[0034] The nanoparticles doped in the base material include SiC nanoparticles, ZrO2 nanoparticles and Si3N4 nanoparticles;

[0035] A Ni-ZrO2 / SiC / Si3N4 composite nano hydrogen barrier inner coating is formed.

[0036] The present invention selects nickel-based oxides or chlorides with high molecular bond energy and dense crystal structure as base materials, which can prevent hydrogen atom penetration. Since the diffusion rate of hydrogen in the nano-doped composite coating is much lower than its diffusion rate in the metal, the present invention dopes SiC, ZrO2 and Si3N4 nanoparticles in the coating, and the C-, O- and N-bonds formed in SiC, ZrO2 and Si3N4, as well as the "hydrogen traps" formed at the interface between the monolayers can effectively inhibit the penetration of hydrogen. In addition, a large number of dangling bonds and molecular vacancies generated by nanoparticle doping can consume the energy of hydrogen atoms, so that they do not have enough energy to break free from the molecular bonds, thereby achieving the capture of hydrogen atoms and ensuring the formation of a material structure that effectively blocks the penetration of hydrogen atoms.

[0037] Further, the doping ratio of the SiC nanoparticles is 1 g / L to 3 g / L;

[0038] The doping ratio of the ZrO2 nanoparticles is 1 g / L to 2 g / L;

[0039] The doping ratio of the Si3N4 nanoparticles is 1 g / L to 3 g / L.

[0040] Furthermore, the average particle size of the SiC nanoparticles, ZrO2 nanoparticles and Si3N4 nanoparticles is 20nm~40nm. Doping nanoparticles of different sizes can refine the grains, reduce the porosity in the ceramic coating, and improve the surface morphology of the ceramic coating, so as to further prevent hydrogen penetration. The average particle size of the nanoparticles is selected to be 20nm~40nm, which forms a new stable molecular structure with the substrate material, blocks the grain boundary channels for hydrogen atom penetration, thereby achieving an effective hydrogen barrier effect.

[0041] Furthermore, the Ni-ZrO2 / SiC / Si3N4 composite nano hydrogen barrier inner coating is prepared by an electrochemical deposition process.

[0042] Furthermore, the deposition liquid formula in the electrochemical deposition process is NiSO4·6H2O: 240-280 g / L, NiCl2·6H2O: 45-60 g / L, H3BO3: 30-40 g / L, sodium dodecyl sulfate: 0.23-0.4 g / L, ZrO2: 20 mL, SiC: 20 mL, and Si3N4: 20 mL.

[0043] Furthermore, the preparation parameters of the electrochemical deposition process are: electrodeposition time is 8 to 10 hours, electrodeposition temperature is 40 to 60°C, and electrodeposition average current density is 10 to 20 mA / cm 2 , the pH value of the electrochemical deposition solution is 9-10, and the stirring speed of the electrochemical deposition solution is 200r / min.

[0044] Example 2

[0045] The embodiment of the present invention also provides a method for preparing a nano hydrogen barrier inner coating of a natural gas pipeline, comprising the following steps:

[0046] (1) Pretreatment of pipe fittings: Prepare a degreasing formula according to a certain ratio, use clean water, degreasing agent, etc. to degrease the pipe fittings to remove surface oil and impurities, and then use sandpaper, grinder, etc. to grind the pipe fittings to ensure that the surface is smooth and free of rust, burrs, oil stains and other impurities;

[0047] (2) Preparation of inner coating: The pipes that have been pre-treated by degreasing and rust removal are placed in an electrochemical deposition solution for preparation. The test uses a constant current pulse power supply and a heating rod to heat the plating solution to 40-60°C. The electroplating time is 8-10 hours. The average current density during the electroplating process is 10-20 mA / cm 2By continuously optimizing the process parameters such as the content of the electrochemical deposition liquid, rotation speed, time, temperature, current density and pH, a Ni-ZrO2 / SiC / Si3N4 composite hydrogen-barrier inner coating with a thickness of 5 to 20 μm and a porosity of <5% is obtained on the inner wall of the pipe fitting, which is tightly bonded to the inner wall of the pipeline. It has the advantages of good hydrogen-barrier performance, strong durability, high bonding, strong density, high smoothness and long service life.

[0048] Furthermore, the degreasing agent has the following formula: OP-1: 0.5 g / L, Na2CO3: 50 g / L, Na3PO4: 70 g / L, NaOH: 10 g / L.

[0049] Furthermore, the formula is NiSO4·6H2O: 240-280 g / L, NiCl2·6H2O: 45-60 g / L, H3BO3: 30-40 g / L, sodium dodecyl sulfate: 0.23-0.4 g / L, ZrO2: 20 mL, SiC: 20 mL, Si3N4: 20 mL.

[0050] Furthermore, the preparation parameters of the electrochemical deposition process are: electrodeposition time is 8 to 10 h, electrodeposition temperature is 40 to 60 ° C, and electrodeposition average current density is 10 to 20 mA / cm 2 , the pH value of the electrochemical deposition solution is 9-10, and the stirring speed of the electrochemical deposition solution is 200r / min.

[0051] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A natural gas pipeline nano hydrogen barrier inner coating, characterized in that: including a base material and nanoparticles doped in the base material; The base material is an oxide or chloride based on nickel; The nanoparticles doped in the base material include SiC nanoparticles, ZrO2 nanoparticles and Si3N4 nanoparticles; A Ni-ZrO2 / SiC / Si3N4 composite nano hydrogen barrier inner coating is formed.

2. A natural gas pipeline nano hydrogen barrier inner coating according to claim 1, characterized in that: The doping ratio of the SiC nanoparticles is 1 g / L to 3 g / L; The doping ratio of the ZrO2 nanoparticles is 1 g / L to 2 g / L; The doping ratio of the Si3N4 nanoparticles is 1 g / L to 2 g / L.

3. The natural gas pipeline nano hydrogen barrier inner coating according to claim 1, characterized in that: The average particle diameters of the SiC nanoparticles, ZrO2 nanoparticles and Si3N4 nanoparticles are 20nm to 40nm.

4. The natural gas pipeline nano hydrogen barrier inner coating according to claim 1, characterized in that: The Ni-ZrO2 / SiC / Si3N4 composite nano hydrogen barrier inner coating is prepared by an electrochemical deposition process.

5. A natural gas pipeline nano hydrogen barrier inner coating according to claim 4, characterized in that: The deposition liquid formula in the electrochemical deposition process is NiSO4·6H2O: 240-280 g / L, NiCl2·6H2O: 45-60 g / L, H3BO3: 30-40 g / L, sodium dodecyl sulfate: 0.23-0.4 g / L, ZrO2: 20 mL, SiC: 20 mL, and Si3N4: 20 mL.

6. A natural gas pipeline nano hydrogen barrier inner coating according to claim 4, characterized in that: The preparation parameters of the electrochemical deposition process are: electrodeposition time is 8 to 10 hours, electrodeposition temperature is 40 to 60°C, and electrodeposition average current density is 10 to 20 mA / cm 2 , the pH value of the electrochemical deposition solution is 9-10, and the stirring speed of the electrochemical deposition solution is 200r / min.

7. A method for preparing a nano hydrogen barrier inner coating for a natural gas pipeline, characterized in that: The steps include: (1) Pretreatment of pipe fittings: Use clean water, degreasing agent, etc. to degrease the pipe fittings, remove surface oil and impurities, and then polish the inner wall of the pipe fittings; (2) Preparation of inner coating: The pipe fittings that have been pre-treated by degreasing, rust removal, etc. are placed in an electrochemical deposition solution for preparation. The electrochemical deposition solution is heated to 40-60°C using a heating rod, and a constant current pulse power supply is used for electrochemical deposition to obtain a Ni-ZrO2 / SiC / Si3N4 composite hydrogen barrier inner coating on the inner wall of the pipe fitting.

8. The method for preparing a nano hydrogen barrier inner coating for a natural gas pipeline according to claim 7, wherein the degreasing agent has the following formula: OP-1: 0.5 g / L, Na2CO3: 50 g / L, Na3PO4: 70 g / L, NaOH: 10 g / L.

9. The method for preparing a nano hydrogen barrier inner coating for a natural gas pipeline according to claim 7, characterized in that: The formula is NiSO4·6H2O: 240-280 g / L, NiCl2·6H2O: 45-60 g / L, H3BO3: 30-40 g / L, sodium dodecyl sulfate: 0.23-0.4 g / L, ZrO2: 20 mL, SiC: 20 mL, Si3N4: 20 mL.

10. The method for preparing a nano hydrogen barrier inner coating for a natural gas pipeline according to claim 7, characterized in that: The preparation parameters of the electrochemical deposition process are: electrodeposition time is 8-10 h, electrodeposition temperature is 40-60 ° C, and the average electrodeposition current density is 10-20 mA / cm 2 , the pH value of the electrochemical deposition solution is 9-10, and the stirring speed of the electrochemical deposition solution is 200r / min.